Endothelin receptor B-deficient mice are protected from high-fat diet-induced metabolic syndrome - Feger, Martina; Meier, Leonie; Strotmann, Jörg; Hoene, Miriam; Vogt, Julia; Wisser, Alexandra; Hirschle, Susanna; Kheim, Marie-Jo; Hocher, Berthold; Weigert, Cora; Föller, Michael (Molecular metabolism, 2024)
Objective - Endothelin receptor B (ETB) together with ETA mediates cellular effects of endothelin 1 (ET-1), an autocrine and endocrine peptide produced by the endothelium and other cells. It regulates vascular tone and controls kidney function. Metabolic syndrome is due to high caloric intake and is characterized by insulin resistance, dyslipidemia, and white adipose tissue (WAT) accumulation. ETA/ETB antagonism has been demonstrated to favorably influence insulin resistance. Our study explored the role of ETB in metabolic syndrome. - Methods - Wild type (etb+/+) and rescued ETB-deficient (etb−/−) mice were fed a high-fat diet, and energy, glucose, and insulin metabolism were analyzed, and hormones and lipids measured in serum and tissues. Cell culture experiments were performed in HepG2 cells. - Results - Compared to etb+/+ mice, etb−/− mice exhibited better glucose tolerance and insulin sensitivity, less WAT accumulation, lower serum triglycerides, and higher energy expenditure. Protection from metabolic syndrome was paralleled by higher hepatic production of fibroblast growth factor 21 (FGF21) and higher serum levels of free thyroxine (fT4), stimulators of energy expenditure. - Conclusions - ETB deficiency confers protection from metabolic syndrome by counteracting glucose intolerance, dyslipidemia, and WAT accumulation due to enhanced energy expenditure, effects at least in part dependent on enhanced production of thyroid hormone/FGF21. ETB antagonism may therefore be a novel therapeutic approach in metabolic syndrome.
Online verfügbar: 28. Dezember 2023, Artikelversion: 8. Januar 2024
Gesehen am 11.03.2025